First Report of Soybean Rust Caused by Phakopsora pachyrhizi on Kudzu (Pueraria montana var. lobata) in Illinois - Bradley, C A (Plant disease, 2010)
Soybean rust, caused by Phakopsora pachyrhizi Syd., first was observed in the continental United States during 2004 on soybean (Glycine max (L.) Merr.) in Louisiana (4), and on kudzu (Pueraria montana (Lour.) Merr. var. lobata (Willd.) Maesen & Almeida) in Florida (2). Kudzu is a leguminous weed that is prevalent in the southern United States with its range extending northward into other states including Illinois. In October 2009, a kudzu patch located in Pulaski County in southern Illinois was investigated for the presence of soybean rust. Twenty-five leaflets were collected, and the abaxial sides of leaflets were evaluated visually for the presence of uredinia with a dissecting microscope. Uredinia and urediniospores were found on two leaflets. When viewed with a compound microscope, urediniospores were hyaline, echinulate, and measured 20 × 25 μm. On the basis of uredinia and urediniospores, the disease tentatively was identified as soybean rust caused by P. pachyrhizi. To confirm the identification, one leaflet with pustules was assayed with a Soybean Rust QuickStix Diagnostic Kit (Envirologix, Portland, ME). For the other leaflet, the area of the pustule was excised (approximately 28 mm2) and an area of the leaflet at the margin on the opposite half of the leaflet with no visible pustule (approximately 54 mm2) was excised. DNA was extracted from the excised areas of the leaflet for confirmation by quantitative PCR (Q-PCR) using primers and probe specific to P. pachyrhizi and P. meibomiae (Arthur) Arthur (1). Both the QuickStix Diagnostic Kit and the Q-PCR confirmed the diagnosis as soybean rust caused by P. pachyrhizi. Q-PCR also suggested the presence of a nonsporulating latent rust infection on the same kudzu leaflet at the margin on the opposite side of the midrib. Soybean rust first was confirmed on soybean in Illinois in 2006 (3), but to our knowledge, this is the first observation of the disease on kudzu in the state. This report confirms that at least some kudzu plants in Illinois are susceptible to soybean rust and that latent kudzu infection may exist without outward signs of the fungus. Currently, this is the most northern observation of soybean rust on kudzu in North America. It is unknown what role, if any, Illinois kudzu will play in the epidemiology of soybean rust in the state. Since kudzu tops die after the first frost, there is no expectation of P. pachyrhizi to overwinter in Illinois on kudzu as it does in some states adjacent to the Gulf of Mexico. References: (1) R. D. Frederick et al. Phytopathology 92:217, 2002. (2) P. F. Harmon et al. Online publication. doi:10.1094/PHP-2005-0613-01-RS. Plant Health Progress, 2005. (3) G. L. Hartman et al. Plant Dis. 91:466, 2007. (4) R. W. Schneider et al. Plant Dis. 89:774, 2005